Сетецентрические технологии управления режимами работы трехфазной сети - Сокол, Евгений Иванович; Сиротин, Юрий Александрович; Иерусалимова, Татьяна Сергеевна; Гриб, Олег Герасимович; Швец, Сергей Викторович; Гапон, Дмитрий Анатольевич (НТУ "ХПИ", 2017)
Интеграция интеллектуальных и сетецентрических технологий в процесс управления режимами работы трехфазной сети обеспечивают оперативность компенсации нелинейностей в системе за счет ортогонального разложения тока и использования метода базисных функций для минимизации потерь.

Procedure for the compensation of the current of zero sequence excludes from circuit the source, as the active component of instantaneous power of zero sequence, and a vector due to a current of zero sequence. This procedure is performed without time delay as it does not require integration. Only a 3-wire system with symmetrical voltage eliminates pulsations and symmetrization of the equivalent conductances of the phases of the task. Under asymmetric voltage, the power is different, its analysis requires the creation of a vector mathematical model of the energy processes of asymmetrical modes of 3-phase systems.
Network-centric technologies for control of three-phase network operation modes
Keywords: беспилотный летательный аппарат; потери; качество; мониторинг; мгновенная мощность; БПЛА; unmanned aerial vehicle; instantaneous power